Lecturers' beliefs and perceptions on formative assessment and their practice in training medical students in a Malaysian university - Ong, Kai Li; Abd Jalil, Khairunnisa Fatini; Hisham, Haris Danial; Mohamad Kasim, Nur Syazana; Idris, Faridah; Adam, Siti Khadijah (Universiti Putra Malaysia, 2023)
Introduction: Formative assessment refers to frequent evaluation of student attainment to identify learning needs. It is crucial for the development of soft skills and improvement in learning progress in the classroom. However, the practice is still lacking and undervalued in medical education. This study aims to determine the level of beliefs and perceived practices of formative assessment among lecturers teaching undergraduate medical programme in a Malaysian university. Methods: A self-administered 27-item questionnaire was distributed to 62 lecturers in a medical school in Selangor, Malaysia. They were required to indicate their agreement and frequency on each item that describes their beliefs on the importance and practice of formative assessment in the medical programme. All data was analysed using IBM SPSS Statistics software version 26. Results: Majority of the respondents indicated that the assessment was conducted frequently during small group sessions (64.5%), through written examination (59.7%) and during practical classes (53.2%). The respondents rated positively on the importance and practice of formative assessment. The score of formative assessment practice through scaffolding was significantly higher than monitoring (Z = 944.5, p < 0.001). There was no significant correlation between beliefs and practice of formative assessment (r(62) = 0.213, p = 0.097). Additionally, the duration of service had no significant association with their perception and practice of formative assessment (p < 0.05). Conclusion: The results of this study suggested that regardless of their level of experience, lecturers exhibited a positive perception of and engagement with formative assessment in training medical students. A substantial improvement of peer and self-assessment practices is warranted to foster student autonomy and accountability on their learning.